PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA KEDAI ALOHA DI KOTA AMBON - Feky Reken; Nadya Nurlailya Ningsih; Ervan Togatorop (Fakultas Ekonomi dan Bisnis Universitas Pancasila Jakarta, 2025)
This study empirically aims to examine the influence of customer satisfaction and price on purchasing decisions at Aloha Café in Ambon City. A quantitative approach was employed, with the research population consisting of consumers who had previously made purchases at Aloha Café. Data collection was carried out by distributing questionnaires using a purposive sampling technique, resulting in a total of 110 respondents. The collected data were analyzed through multiple linear regression, classical assumption tests, hypothesis testing, and the coefficient of determination (R²), with the assistance of SPSS version 26 software. The findings indicate that, partially, both customer satisfaction and price exert a positive and significant effect on purchasing decisions at Aloha Café in Ambon City